On plain lattice points whose coordinates are reciprocals modulo a prime - Fujii, Akio; Kitaoka, Yoshiyuki (Nagoya mathematical journal, 1997)
We consider, for a given large prime p, the problem of covering a square [0, p] × [0, p] with discs center at the lattice point (x, y), x and y subject to condition xy ≡ 1 (mod p) and with radius r. We are concerned with the size of r.